Escisión de torus mandibular bilateral en paciente sistémicamente comprometido: reporte de caso - Jiménez-Castellanos, Fabio Andrés (2020)
The mandibular torus is a bony exophytic growth located in the lingual area of the mandible. While this growth is generally bilateral, it can be associated with temporomandibular disorders. I It affects pronunciation, produces halitosis, interferes with swallowing, and causes pain in themucosa under poorly designed prostheses. Normally, treatment is not necessary, except in cases with prosthetic needs, functional problems, food retention, phonetic disorders or if it is to be used as an autologous bone graft. The aim of this study was to perform a bilateral mandibular torusexcision in a systemically compromised patient for subsequent rehabilitation with a removable partial denture. A 66-year-old female presenting a bilateral mandibular torus attended our dental clinic. After achieving the diagnosis and analyzing the scientific evidence available, the bilateralmandibular torus was atraumatically excised, allowing correct seating of a removable partial denture. Bilateral mandibular torus excision is a safe and effective procedure, which helps to avoid prosthetic complications involving structural design and biological complications such as ulcers,food deposits and / or halitosis, restoring stability and function to the stomatognathic system.